ON THE ATTITUDE OF FOREIGN LITERARY SCHOLARS TO THE HERITAGE OF JADID LITERATURE - Usmonov G’iyosiddin Murotjonovich (International Journal of Literature and Language Studies, 2026)
This article discusses the attitude of foreign scholars to the representatives of 20th-century literature, particularly the heritage of Jadid literature, and the translation of our writers' works by them into English, German, French, and a number of other foreign languages.